Echinoderms from Lobos de Afuera islands (Lambayeque, Peru) - Hooker, Yuri (2005)
A rapid survey in Islas Lobos de Afuera (06°55,5 S - 80°42,5 W) were carry out from June 19 to 24 of 1999. A total of 39 Echinodermata species was collected: 7 Asteroidea, including two new records for Peru, Luidia bellonae, Luidia brevispina; 8 Ophiuroidea, whit one new record for Peru Ophionereis sp.; 11 Echinoidea, including five new records for Peru, Astropyga pulvinata, Diadema mexicanum, Lytechinus sp., Toxopneustes roseus, Tripneustes depressus; and 13 Holoturoidea, including six new records, Psolidium dorsipes, Cucumaria flamma, Pseudocnus californicus, Holothuria sp., Chiridota sp. and Actinopyga sp.